Alternative splicing triggered by the insertion of a CACTA transposon attenuates LsGLK and leads to the development of pale‐green leaves in lettuce. (17th November 2021) - Zhang, Lei; Qian, Jinlong; Han, Yuting; Jia, Yue; Kuang, Hanhui; Chen, Jiongjiong
SUMMARY: Lettuce ( Lactuca sativa ) is one of the most important vegetable crops in the world. As a leafy vegetable, the polymorphism of lettuce leaves from dark to pale green is an important trait. However, the genetic and molecular mechanisms underlying such variations remain poorly understood. In this study, one major locus controlling the polymorphism of dark‐ and pale‐green leaves in lettuce was identified using genome‐wide association studies (GWAS). This locus was then fine mapped to an interval of 5375 bp on chromosome 4 using a segregating population containing 2480 progeny. Only one gene, homologous to the GLK genes in Arabidopsis and other plants, is present in the candidate region. A complementation test confirmed that the candidate gene, LsGLK, contributes to the variation of dark‐ and pale‐green leaves. Sequence analysis showed that a CACTA transposon of 7434 bp was inserted 10 bp downstream of the stop codon of LsGLK, followed by a duplication of a 1826‐bp fragment covering exons 3–6 of the LsGLK gene. The transposon insertion did not change the expression level of the LsGLK gene. However, because of alternative splicing, only 6% of the transcripts produced from the transposon insertion were wild‐type transcripts, which led to the production of pale‐green leaves. An evolutionary analysis revealed that the insertion of the CACTA transposon occurred in cultivated lettuce and might have been selected in particular cultivars to satisfy the diverse demands of consumers. In this study, we demonstrated that a transposon insertion near a gene may affect its splicing and consequently generate phenotypic variations. Significance Statement: As a leafy vegetable, the polymorphism of lettuce leaves from dark to pale green is an important trait. We report that a CACTA transposon inserted into the 3'‐UTR of LsGLK triggered considerable alternative splicing and led to the development of pale‐green leaves. These results provide new insights into the roles and mechanisms of transposons on gene function and phenotypic variation.